2008
DOI: 10.1111/j.1754-7121.2008.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Public‐private partnerships in Canada: Theory and evidence

Abstract: This article develops some theory on and examines the implementation and performance of Canadian public-private partnerships (P3s). It focuses primarily on infrastructure projects and addresses three questions: 1) What goals do governments expect to achieve through P3s? 2) How effective are P3s likely to be at delivering value to governments and citizens? 3) What lessons can be derived from the use of P3s? The article reviews the government's intended social goals for P3s and evaluates how effective P3s have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 31 publications
0
93
0
Order By: Relevance
“…Procurement is significantly more complex than construction academics would wish it to be -the variability is such, it is argued, that it is virtually impossible to classify procurement by any sort of rational positivistic approach". This finding also holds for PPPs, as once the underlying characteristics of PPPs are taken into consideration, wide variations can be seen to exist when they are compared to each other [3]. Traditional approaches to procurement, which attempt to link different types of infrastructure procurement (such as PPPs or alliances) do not take into account the complexity and variation possible between projects, and this failure to take into account the all of the variables involved in projects results in considerable difficulties in assessing and comparing the performance of different projects.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Procurement is significantly more complex than construction academics would wish it to be -the variability is such, it is argued, that it is virtually impossible to classify procurement by any sort of rational positivistic approach". This finding also holds for PPPs, as once the underlying characteristics of PPPs are taken into consideration, wide variations can be seen to exist when they are compared to each other [3]. Traditional approaches to procurement, which attempt to link different types of infrastructure procurement (such as PPPs or alliances) do not take into account the complexity and variation possible between projects, and this failure to take into account the all of the variables involved in projects results in considerable difficulties in assessing and comparing the performance of different projects.…”
mentioning
confidence: 75%
“…[19], [20] and [3] have already identified several key elements of any type of procurement project which will be used to analyse PPPs. These elements of PPPs are set out in Table 1 below, together with the various options available in each 'gene', and an explanation of each element follows.…”
Section: Conceptualisation Of Ppps As Routinesmentioning
confidence: 99%
See 1 more Smart Citation
“…is the government's debt. Though there is some disagreement on whether PPPs are more cost-efficient in the short run (Vining and Boardman, 2008), we assume that PPPs are more efficient over time given high institutional quality and incorporate as a cost multiplier on PPPs, representing the effects of institutional quality. As such, 1 < represents higher institutional quality while < 1 represents lower institutional quality.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The borough in question is notorious for its poor transport links within the area and a number of residents' campaigns have begun campaigning against plans to close local GP surgeries. Vining and Boardman (2006) found that P3 (PPP in Canada) often involved high transaction costs, which were aggravated by complexity and by firms attempting to transfer risk (e.g. through setting up specialised companies and through maintaining high debt-to-equity ratios).…”
Section: Introductionmentioning
confidence: 99%